Islam and Politics in the Middle East - Arief Bakhtiar Darmawan (Journal of Governance and Public Policy, 2018)
This paper aims to analyze religion’s roles related to the political activities in the contemporary Middle East. Constructivism is a framework that offers the way to understand the phenomenon. Constructivism provides a place for the influence of non-material factors such as the value, identity, and purpose of actor behavior in politics. In this article, the author examines through two levels of analysis, ie state level and regional level. At the state level, Islamic political ideology grows in a modern state and often confronts democracy. The debate over the application of Islamic law, the involvement in elections, and the adaptation of Islamic justice principles and the principle of equality are the discourses that characterize political activity in the Middle East. At the regional level, Islam exerts impact in foreign policy in the region. The regional tensions between Sunni and Shiite groups, the resistance in the context of jihad, and the emergence of ISIS are part of the conflict that contributes to regional instability. These political behaviors shows that Islam is not a religion with a single interpretation.Keywords: Islam, Middle East, constructivism, modern states, foreign policy